Influência dos movimentos condilares e mandibulares na via aérea superior durante a utilização do aparelho de avanço mandibular no tratamento para apneia obstrutiva do sono - Pereira, Amanda Barbosa (2023)
Obstructive sleep apnea (OSA) is a respiratory disorder characterized by partial or complete obstruction of the upper airway (UA), preventing normal ventilation during sleep. It manifests as a partial reduction (hypopnea) or complete cessation (apnea) of respiratory airflow, resulting in cortical arousals and/or a drop in blood oxygen saturation. The treatment of OSA is determined by the severity of the disease, as well as the patient's cooperation and interest. The most commonly used intraoral appliances (IOAs) are mandibular advancement devices (MADs), which act by promoting mandibular protrusion, thereby increasing the volume of the UA. This study aimed to evaluate the influence of condylar and mandibular movements on the UA during the use of MAD for the treatment of OSA. Twenty patients with OSA were prospectively treated with MAD. Clinical examinations, cone-beam computed tomography, and polysomnography were performed before MAD treatment and after obtaining therapeutic protrusion. Polysomnographic variables and three-dimensional measurements of the temporomandibular joint, mandible, and UA were analyzed statistically. Condylar rotation and anterior translation, as well as anterior mandibular displacement, were directly correlated with the total volume of the UA, while vertical mandibular translation was inversely correlated with the volume of the inferior oropharynx. MAA resulted in an increase in the volume and area of the superior oropharynx (SO). There was no statistically significant correlation between condylar rotation/translation and polysomnographic variables. With MAD, there was a significant increase in vertical dimension, changes in condylar position (rotation and translation), and mandibular displacement. The central and medial lengths of the articular eminence were inversely correlated with condylar rotation and translation, respectively. The lateral length of the eminence was directly correlated with condylar translation, and the lateral height was directly correlated with condylar rotation and translation. This study allows us to conclude that condylar and mandibular movements exerted an influence on the UA. Furthermore, the articular eminence played a role in the amount of condylar rotation and translation, indicating the need for anatomical evaluation of patients prior to choosing MAD treatment for more favorable outcomes in the therapy of OSA.